Gambaran Pemilihan Bahan dan Higienitas Pengolahan Makanan Balita di Posyandu Wonotingal Kecamatan Candisari Semarang - Devi, Chindya Paramitha; Untari (Universitas Ngudi Waluyo, 2025)
Nutritional problems in Indonesia occur due to various factors, such as food intake, environment including hygiene and sanitation, socio-economic, family characteristics, and the presence of infection. Children who have poor nutritional status are susceptible to infection, because children were lack of immunity. Conversely, children who suffer from infections do not have sufficient appetite, resulting in children being malnourished and falling into poor nutritional status. So, infection and nutritional status were correlated. Malnutrition in children is influenced by the level of knowledge, attitudes and behavior of mothers in choosing the right food ingredients. The practice of selecting ingredients and hygiene of food processing is closely related to the emergence of certain diseases or infections, so further research is needed. This descriptive study focused on the description of the selection of ingredients and processing of toddler food by mothers, which wass carried out using a research instrument in the form of a questionnaire. The results of the study of 20 respondents (mothers of toddlers) conducted at the Posyandu of Wonotingal Village regarding the practice of mothers in preparing food for children (toddlers) were classified as